CONTRIBUIÇÕES DO PROCESSO DE HARMONIZAÇÃO DA REGULAMENTAÇÃO DE GÁS NATURAL VEICULAR NO MERCOSUL - Oliveto, Italo Domenico (2009)
Natural gas for automotive sector (GNG), had its use in the MERCOSUR area began in Argentina in the 80s. During this period, as the only participant in this sector, this country stood out in this trade, given a national energy policy in its favor. In another phase, Brazil the second incoming as early as the 80th, increased the exchange and promoted technology and development for natural gas in the MERCOSUR. Then, Brazil and Argentina, were facing the necessity of definition and implementation of rules that could be adopted by all in this region. Therefore, these countries began the process of harmonization of regulations for the use of CNG in the MERCOSUR. This work aims to analyze the effect of the harmonization process of regulations and the approach to removing technical and economic integration in this area. This study addressed the evolution and development of CNG in Brazil and Argentina, as an alternative energy for vehicular use. This work is based on bibliographical review and information obtained through interviews with experts from public and private sector, aims to demonstrate the perception of the implementation of uniform regulations for the use of CNG in MERCOSUR. In this sense, the results indicated that 91% of respondents of this research confirmed that the harmonized regulations in the MERCOSUR increase the flow of vehicles at the borders of this region. Furthermore, 62% of those interviewed confirmed that the current distribution of natural gas is not sufficient to meet demand retracted by the use of CNG. Finally, the results of research show that despite the efforts of government and private sectors should be established by the governments of MERCOSUR, a policy on behalf of CNG in this area.